The library's new role: As a supporter of collaboration and innovation activities - Nurida Maulidia Rahma; Cipta Endyana; Dicky Muslim (Record and Library Journal, 2022)
Background of the study: Innovation is very important for efforts to increase the economy. One way to create innovation is to carry out collaborative activities. Shared workspaces or also known as coworking spaces facilitate collaboration activities. Although many libraries have adopted the concept of a co-working space, it is still not fully aware that library managers are responsible for collaboration and innovation. Therefore, it is considered as a collection storage area so that it is not involved in the development of the innovation ecosystem. Purpose: This study aims to determine whether the library participates in collaboration and innovation activities. Method: The research method used to answer questions and test opinions is a systematic review. The articles used are 21 articles. Findings: The results show that the library is a place for collaboration and innovation to occur. So that the library has a role in the creation of collaboration and innovation. Conclusion: The library's new role is to support collaboration and innovation activities.